ANALYSING GRAMMAR MISTAKES ON WRITTEN WORKS OF ELEMENTARY STUDENTS - Agustia Widiastuti; Dedy Setiawan (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2016)
Students make mistakes because they practice to produce the language. However, sometimes the students do not realize that they make mistakes when they do exercises. Hence, they need to be shown on the mistakes as parts of the feedback that the teacher give in a process of teaching and learning. Written works of elementary students to a certain extent are similar with the spoken language that they produce when they practice. Accordingly, analyzing the grammar mistakes on written works of the language students of elementary level is very useful as it can be used as input for elementary students when they learn to communicate both in oral and written. The present study is an attempt to find out the mistakes that the students make on the basis on their written productions. The result shows there some grammatical aspects that the students constantly produced. As their elementary written work is similar with that in their spoken language, the present study will be beneficial for language teachers in pre-assuming and emphasizing on what to teach in elementary level. Keywords: language errors/mistakes, feedback, written works, elementary students